Participatory Research Methods: A Methodological Approach in Motion - Bergold, Jarg; Thomas, Stefan (Forum Qualitative Sozialforschung / Forum: Qualitative Social Research, 2012)
This article serves as an introduction to the FQS special issue "Participatory Qualitative Research." In recent years there has been a resurgence of interest in participatory research strategies. The articles in this special issue come from different disciplines. Against the background of concrete empirical research projects, they address numerous conceptual considerations and methodological approaches. After reading the contributions, and engaging with the authors' arguments, we were prompted to focus in particular on those areas in which further work needs to be done. They include, on the one hand, fundamental principles of participatory research, such as democratic-theory considerations, the concept of "safe space," participation issues, and ethical questions. And, on the other hand, we focus on practical research considerations regarding the role and tasks of the various participants; specific methodological approaches; and quality criteria—understood here in the sense of arguments justifying a participatory approach. Our aim is to stimulate a broad discussion that does not focus only on participatory research in the narrower sense. Because participatory methodology poses certain knowledge- and research-related questions in a radical way, it has the potential to draw attention to hitherto neglected areas in qualitative methodology and to stimulate their further development.URN: http://nbn-resolving.de/urn:nbn:de:0114-fqs1201302
Number: 1
Keywords: Focus group; Normes éthiques; Participation; Participatory research methods; marginalization

Creative Collaboration - Yong, Titus (Encyclopedia of Creativity, Invention, Innovation and Entrepreneurship, 2020)
Creative collaboration happens when a creative process is undertaken by two or more individuals, teams, entities, or organizations for a project or challenge of common concern. Typically, the project is too challenging to be undertaken alone; and if done satisfactorily, the outcome is would be both novel and useful. Members can collaborate either physically or remotely through electronic (online creative collaboration) or other means at all or different phases of the project.
Keywords: Co-création; Innovation; Participation; Réservé UdeM